1982
DOI: 10.2337/diacare.5.2.s135
|View full text |Cite
|
Sign up to set email alerts
|

The U.S. “New Patient” and “Transfer” Studies

Abstract: The large-scale clinical trials of human insulin (recombinant DNA) in the United States consisted of a "New Patient" study and a "Transfer" study. The "New Patient" study involved 101 patients (38% type I) who have never received insulin and who were treated with human insulin and followed for 6 mo using NPH insulin alone or in combination with Neutral Regular Insulin (NRI). Shortly after treatment, serum glucose and total glycohemoglobin concentration fell. No patients developed insulin lipoatrophy or insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The preparations were a long-acting zinc human insulin (Ultratard HM) and an intermediate isophane human insulin (Protaphane HM) having a longer duration compared with other human isophane insulins (12,13); both were mixed with soluble insulin in the evening injection before dinner. The preparations were a long-acting zinc human insulin (Ultratard HM) and an intermediate isophane human insulin (Protaphane HM) having a longer duration compared with other human isophane insulins (12,13); both were mixed with soluble insulin in the evening injection before dinner.…”
Section: Control Of Early-morning Hyperglycemiamentioning
confidence: 99%
“…The preparations were a long-acting zinc human insulin (Ultratard HM) and an intermediate isophane human insulin (Protaphane HM) having a longer duration compared with other human isophane insulins (12,13); both were mixed with soluble insulin in the evening injection before dinner. The preparations were a long-acting zinc human insulin (Ultratard HM) and an intermediate isophane human insulin (Protaphane HM) having a longer duration compared with other human isophane insulins (12,13); both were mixed with soluble insulin in the evening injection before dinner.…”
Section: Control Of Early-morning Hyperglycemiamentioning
confidence: 99%
“…Since lipohypertrophy is due largely to the local pharmacologic (lipogenic) effects of insulin, 2 this is not surprising and, indeed, lipohypertrophy has recently been reported in patients receiving only human insulin. 3 Lipohypertrophy will therefore continue to be a side effect of subcutaneous insulin administration. In clinical practice we have noticed that the insulin requirements of patients sometimes fall abruptly when they are advised to avoid their lipohypertrophied injection sites.…”
mentioning
confidence: 98%
“…Even human insulin has the capacity to elicit antibody formation, at least when given subcutaneously, 30 ' 31 and it has been shown that in patients presensitized to insulin (as in our patient), even the highly purified animal insulins or human insulin may result in local allergic reactions. 32 " 34 Thus, highly purified animal insulins and human insulin have not completely eliminated the potential and actual immunologic problems associated with exogenous insulin administration.…”
Section: Resultsmentioning
confidence: 90%